Conjunctive use of tank and well water in tank irrigation systems - Palanisami, K. (International Food Policy Research Institute, 1990)
Tank irrigation systems in southern India are centuries old. They account for over 30 percent of th( total irrigated area of Tamil Nadu, Karnataka, and Andhra Pradesh states. These tanks are mainly used to irrigate rice during the late monsoon to early dry season from September to December.